Attitude towards reciprocity as a motive for oocyte donation. (June 2018) - Pennings, Guido; Ravel, Célia; Girard, Jean-Maxime; Domin-Bernhard, Mathilde; Provoost, Veerle
Abstract: Objective: Finding out whether patients would be motivated by reciprocity when considering donating oocytes to others. Study design: This is a prospective monocentric study in the CECOS of the Centre Hospitalier Universitaire (CHU) of Rennes (France) on the opinion of patients regarding reciprocity. Couples who had a child with donor sperm were asked whether they would consider oocyte donation as a way of giving something back. Results: Twenty six couples and one man answered the questionnaire. About half of the respondents (49%) felt that they should contribute to the system from which they benefitted. Although the patients would benefit from a reduction in waiting time, this advantage was only important for one in four persons. The only items on which the answers between men and women were significantly different concerned the results of the donation: women would think more often about the potential recipient and the child and they more often wanted to know whether children were born from their donation. Conclusion: The results show that beside altruism, reciprocity may be an important moral reason for people to donate gametes.